Usnea aurantiaco-atra (Jacq) Bory: Metabolites and Biological Activities - Vega Bello, Maria Jesus; Moreno Sancho, María de la Luz; Estellés Leal, Rossana; Hernández Andreu, José Miguel; Prieto Ruiz, Jesús Ángel (Molecules, 2023)
Background: Lichens are complex symbiotic associations between a fungus and an alga or cyanobacterium. Due to their great adaptability to the environment, they have managed to colonize many terrestrial habitats, presenting a worldwide distribution from the poles to the tropical regions and from the plains to the highest mountains. In the flora of the Antarctic region, lichens stand out due to their variety and development and are a potential source of new bioactive compounds. Methods: A phytochemical study of the Antarctic lichen Usnea aurantiaco-atra (Jacq) Bory was conducted with the intention of determining the most important metabolites. In addition, the cytotoxic and antioxidant activities of its extracts were determined. Results: Cytotoxicity studies revealed that the hexane extract contains usnic acid as a majority metabolite, in addition to linoleic acid, ergosterols and terpenes, and demonstrates cytotoxic activity against an A375 melanoma cell line. On the other hand, the presence of total phenols in the extracts did not influence their antioxidant activity. Conclusions: U. aurantiaco-atra contains mainly usnic acid, although there are terpenes and ergosta compounds that could be responsible for its cytotoxic activity. The presence of phenols did not confer antioxidant properties. This work was supported by Catholic University of Valencia “San Vicente Mártir” (Grant number: 2011-011-012). Biotecnología